Elaboración de propuesta para la producción de cerveza artesanal tipo ale con base en malta pale ale y almidón de papa sabanera. (2022)
In this degree work, the proposal for the production of craft ale beer with pale ale malt and sabanera potato starch is presented, describing the beer production process with its raw materials, stages, and quality standards governed by decree 1686 of 2012. Initially, the physicochemical characteristics that the main raw materials must have for the production of this type of beer are presented. Then, all the necessary stages in the production process of potato starch and craft beer are presented, taking into account the yield in terms of the degree of alcohol that can be produced. Finally, the financial analysis of the proposal is shown, where it is estimated that the production value of the proposal is $ 6.200 Cop and looking for a profit margin of 20%, the cost of trade is $ 7.300 Cop. It is determined that it is possible to develop a craft beer with potato starch and pale ale malt being a viable and economically sustainable process.